Clinical insight into hypercalcemia in children - Huseyin Anıl Korkmaz (Endokrynologia Polska)
Plasma calcium levels are regulated by many factors, including the levels of calcium-sensitive receptors, parathyroid hormone, parathyroid hormone receptors, vitamin D, vitamin D receptors, and other proteins. Plasma calcium is also related to genetic structure; albumin, creatinine, and phosphorus levels; and blood pH. Multiple factors affect hypercalcemia in children, making its management challenging. These factors have led to accurate diagnosis for mostly mild and moderate cases of hypercalcemia, resulting in a management dilemma. In many clinics, physicians face undiagnosed cases of hypercalcemia even if the hypercalcemia algorithms are followed accurately. In this narrative review, we discuss a logical approach to the investigation and subsequent clinical management of hypercalcemia in children.